Evaluation of Ficus minahassae Fruit Extract as a Natural Agent against Propionibacterium acnes - Abigail F. Maarisit; Cliveno Kojongian; Tesalonika Rondonuwu; Intan J. F. Rawung; Reine Kalalo; Arter Supit; Silvana L. Tumbel; Wilmar Maarisit (FMIPA UKIT, 2025)
Ficus minahassae fruit is known to contain bioactive compounds that have the potential to act as antibacterial agents. This study aims to determine the antibacterial activity of Propionibacterium acnes from F. minahassae fruit extract. F. minahassae fruit is extracted using ethanol. Antibacterial activity test using the disc diffusion method. Based on the results of the study, it was obtained that F. minahassae fruit extract was able to inhibit P. acnes bacteria at concentrations of 200, 300, 400, 500, and 600 mg/disc with inhibition zone diameters of 11.68, 13.33, 14.35, 15.47, and 17.82 mm, respectively. F. minahassae fruit extract can be developed as a raw material for drugs, especially anti-bacterial P. acnes, which causes acne.